PENCIPTAAN MOTIF BATIK DENGAN SUMBER IDE MASJID AGUNG GRESIK - Aliya Putri, Shofi; Arifiana, Deny; Nahari, Inty; Nashikhah, Ma’rifatun (Jurnal Socia Akademika, 2025)
This research is a creative study that aims to describe the stages and results of designing batik motifs inspired by architectural elements of the Gresik Grand Mosque. The creative process was carried out through three main stages: exploration (including concept formulation, technique selection, and material identification), design (from sketching, motif development, to pattern arrangement), and realisation (including the batik-making process, dyeing, wax removal, drying, and finalising the product into batik sarongs). The resulting works are three hand-drawn batik sarongs, namely Agungwara 2, Agungwara 4, and Agungwara 7. All three employ similar basic motifs, but are composed with distinct elements, resulting in unique visuals in each work. Agungwara 2 highlights the shape of a mosque roof and protective ornaments as symbols of tranquillity and spiritual values. Agungwara 4 features hourglass and mihrab motifs that reflect the meanings of time, light, and the direction of worship. Meanwhile, Agungwara 7 combines images of a mosque, gate, and floral elements that symbolise the strength of faith, knowledge, and harmony. The entire collection reflects a blend of aesthetic values, spirituality, and local wisdom in a contextual and functional visual form.